Studi Perencanaan Campuran Latasir (Lapisan Tipis Aspal Pasir) Pada Pekerjaan Peningkatan Jalan Desa Terpencil Di Kabupaten Tapin - Hudan Rahmani; Hendra Cahyadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Candi Laras Utara sub-district, includes swampy lowlands, are very difficult to reach by using a 4-wheeled vehicle because the conditions of the roads are not standard or in narrow terms and the traffic volume can be said to be very low because it is only passed by 2-wheeled vehicles, the alternative is to use a Latasir pavement layer as a surface layer, there are 3 problems that must be examined, including how to plan the composition of the Latasir-forming material mixture, and how to transport the material to the road work location. and how to process the Latasir material, method The logic of this research is an experimental method, namely the processing of test objects in the form of samples of various variations in the form of surface or road surface layers, but previously all the materials that make up these samples were also tested in the laboratory as well as their quality. It was concluded that the asphalt content that met the requirements for the best quality of this Latasir was 7%, 710 kg stability, 6.170% air cavity, the quotient for marshall was 3.533 KN / mm, mixed density 2.183 kg / dm³ and melting 2.890 mm.